Definitory Characteristics of Pianistic Expression in the Contemporary Jazz - BĂLAN, Florin (Studia Universitatis Babes-Bolyai Musica, 2023)
The general fundamental approach of improvisation, of the creative moment in jazz leads succinctly to the question of whether this phenomenon is a product or a process. The jazz perception as a product assumes that the recordings accompanied by the related transcripts represent that product (final) which is used for analytical purposes by taking harmonical-melodical characteristics. It is important to remember the aspect by which these transcripts do not fully express the essence of improvised thinking and elaboration but are only a starting point in identifying key characteristic features. The possibility of representing a replica of the artistic act produced on stage, however, is not a real one. Visualizing the improvisation process as a practical way of creative performance is therefore an essential aspect of the artistic act. This should be considered together with the product, especially when synthesizing models or indicators that define the personal style of the instrumentalist. Previously, some jazz critics defined the vision of the two modes as an inseparable dichotomy, which is the basis of multi-dimensional analytical possibilities. Beginning in the ’60s, jazz is marked in the expression and elaboration of pianistics by Herbie Hancock, Chick Corea, Bill Evans and later by Keith Jarrett. They implement a variety of contemporary jazz elements, melodical-harmonic expressions that will be taken over and will obviously lead to a new evolutionary stage.